Floorgasm: Queer(s), solidarity and resilience in punk. (November 2017) - Sharp, Megan; Nilan, Pam
Abstract: This article explores queer(ed) punk scenes, primarily in Australia. Queer ciswomen, transwomen and non-binary people aged 20–30 years are the informants here in a feminist-informed ethnographic study. They were found to engage strategies of resistance against cismale dominance at punk gigs and events in order to claim queer(ed) territory. In brief, they worked collectively to subvert the dominant patriarchal norms in punk spaces. They mobilised community-building through the politics of Do-It-Together (DIT) as a radical reshaping of the traditional punk ethos of DIY (Do-It-Yourself). They also worked to make gigs more queer-affirmative through mobilising the initiative of safe(r) spaces. We map some queer collective resilience in punk to authorise the expression of counter-hegemonic gender identities. The gig outcome was pleasurable queer solidarity enmeshed with music, a kind of metaphysical 'floorgasm'. Highlights: Queerness is locatable in an authorised map of punk space; brought together and pulled apart by embodiments & (re)actions. Queers actively engage in making and (re)claiming space and time, curating long-lasting positive and pleasurable identities. Punk + queer produces collaboratively accomplished affective intensities and a metaphorical space that transcends materiality.